The Geopolitics of Iraqi Foreign Policy: The Mediation Model between Saudi Arabia and Iran - Alzubaidi, Ammar (Al-Adab Journal, 2024)
This study examines the geopolitics of Iraqi foreign policy as a means of mediation between Saudi Arabia and Iran. The research focuses on the role played by Iraq as a mediator between the two regional states in light of the political and security challenges facing the region. The geopolitical factors that influence Iraqi foreign policy are analyzed and form the basis for its role as a mediator. Bilateral relations between Iraq and both Saudi Arabia and Iran are being studied. Including shared interests and tensions, and identifying potential points for reaching political settlements or solutions. Analysis of erosion is provided to identify potential points for reaching political settlements or solutions. An analysis of the regional shifts affecting Iraq is provided and plays a role in providing support as a mediator. Iraq has an important geographical location and a long culture, which enhances the possibility of playing an active role in the mediation between Saudi Arabia and Iran. The study reached multiple conclusions indicating that stability in the region requires the role of Iraq as a neutral and effective mediator to help in a political settlement and maintain security and peace in the Middle East. One of the important conclusions is that Iraq's position on the energy map will have a role in determining the course of settlement in Iraq and the region. The Iraqi mediation led by Prime Minister Mustafa Al-Kadhimi succeeded in bringing the Saudi and Iranian parties together and taking clear steps towards re-normalizing relations during five years of bilateral talks in Baghdad.